2012
DOI: 10.1093/ehjci/jes189
|View full text |Cite
|
Sign up to set email alerts
|

Association of left ventricular diastolic function with systolic dyssynchrony: a population study

Abstract: We demonstrated that in unselected subjects LV diastolic dysfunction was associated with mechanical LV dyssynchrony as assessed by echocardiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…This finding is consistent with the findings reported by Kuznetsova et al [29],. who reported that, in a study population with LV diastolic dysfunction, females had greater dyssynchrony compared with males.…”
Section: Discussionsupporting
confidence: 94%
“…This finding is consistent with the findings reported by Kuznetsova et al [29],. who reported that, in a study population with LV diastolic dysfunction, females had greater dyssynchrony compared with males.…”
Section: Discussionsupporting
confidence: 94%
“…The prolonged diastolic and systolic dyssynchronies indicate energy wastage resulting from LV dyssynchrony, which may lead to a reduction in cardiac energy reserves 11 . Moreover, a reduction in systolic shortening resulting from deteriorated dyssynchrony has been shown 26 . Despite a more decreased LV longitudinal systolic function, a more prolonged systolic dyssynchrony was observed in HFrEF patients compared to HFpEF patients in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Temporal heterogeneity in systolic function interrupts the normally coordinated relationship between systolic shortening and diastolic lengthening . A reduction in systolic shortening resulting from deteriorated dyssynchrony has been shown to increase LV filling pressure . We also found that LV systolic function was significantly correlated with LV diastolic and systolic dyssynchrony.…”
Section: Discussionmentioning
confidence: 50%
“…30,31 A reduction in systolic shortening resulting from deteriorated dyssynchrony has been shown to increase LV filling pressure. 32 We also found that LV systolic function was significantly correlated with LV diastolic and systolic dyssynchrony. In addition, plasma NT-pro-BNP was correlated with both Te-SD and LV systolic longitudinal strain, suggesting a relationship between systolic and diastolic dysfunction.…”
Section: Ta B L E 3 Comparison Of Left Ventricular Function and Dyssymentioning
confidence: 52%